Populism as ideology: relations and reflections - Mavridis, Iraklis (The Greek Review of Social Research, 2025)
This essay is an attempt to tackle the complex issue of the relations between populism and ideology, through two specific conceptualizations of ideology, and we aim to examine several ideas concerning conceptual problems as well as functions of ideology within the socio-political field. Our argument, provisionally, is that there are similarities and analogies between the two discursive formations, and we propose that populism can indeed be considered as a form of ideological discourse, maybe not in the sense of a “hard” political ideology but as a “thin” one.